Association Between Neonatal Arrhythmia and Mortality and Recurrence: A Retrospective Study - Ran, Lihong; Li, Jie; Bao, Lei; Chen, Long (Frontiers in Pediatrics, 2022)
Objective The aim of the present study was to explore the association between neonatal arrhythmia (NA) and mortality and recurrence. Methods A single-center, retrospective study was performed between Jan-01, 2015 and Dec-31, 2019. Neonates with NA were eligible and divided into either benign or non-benign groups. The primary outcomes were mortality and recurrence within 2-6 years. Results NA was diagnosed in 189(0.39%) patients after screening 47911 hospitalized neonates, and ten of them did not finish the follow-up. Finally, 179 neonates were included into the final analysis (58 in non-benign NA and 121 in benign NA groups). The incidences of death and recurrence for NA were 5.59%(10/179) and 18.44%(33/179). Compared with neonates with benign NA, those neonates with non-benign NA were shown higher rates of death (13.79% vs 1.65%; OR: 5.73, 95%CI: 1.07, 31.01, p = 0.04) and recurrence (44.83% vs 5.79%; OR: 8.49, 95%CI: 3.12, 23.08, p < 0.001). Conclusions Neonates with non-benign NA were shown higher rates of death and recurrence when compared with benign NA. Due to high recurrence, more attention was needed in neonates with non-benign NA after discharge.